Agile Processes in Software Engineering and Extreme Programming: 19th International Conference, XP 2018, Porto, Portugal, May 21-25, 2018, Proceedings - Garbajosa, Juan; Wang, Xiaofeng; Aguiar, Ademar (Lecture Notes in Business Information Processing, 2018)
agile software development; test-driven development; project and people management; empirical software engineering; continuous experimentation